2018
DOI: 10.1051/shsconf/20184200067
|View full text |Cite
|
Sign up to set email alerts
|

The Implications Of Politeness Strategies Among Teachers And Students In The Classroom

Abstract: Abstract. Politeness was needed to be implemented since rudeness creates conflict between teacher and students. Politeness also used in order to teach students the way of being polite, and redress the conflict in conversation. This study aimed at analyzing the implication of using politeness strategies on teaching and learning process. The subjects of this study were the tenth grade teacher and students of SMK Nusa Dua Bali. The data were in the form of conversations among the subjects in their interactions du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
(3 reference statements)
0
7
0
1
Order By: Relevance
“…Studies on politeness also have been conducted by some researchers in Indonesia (Ambarwati et al, 2019;Jeanyfer & Tanto, 2018;Khusnia, 2017;Mahmud, 2019;Umayah et al, 2018;Widiadnya et al, 2018). Some researchers found that students in higher and secondary education showed positive and negative politeness strategies in their classroom interactions (Khusnia, 2017;Mahmud, 2019;Umayah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on politeness also have been conducted by some researchers in Indonesia (Ambarwati et al, 2019;Jeanyfer & Tanto, 2018;Khusnia, 2017;Mahmud, 2019;Umayah et al, 2018;Widiadnya et al, 2018). Some researchers found that students in higher and secondary education showed positive and negative politeness strategies in their classroom interactions (Khusnia, 2017;Mahmud, 2019;Umayah et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They elaborated politeness strategies in the social media platform as a process to show how people choose appropriate speech, maintain the power in doing communication and maintain the attitude to save interlocutor's face. In addition, Widiadnya et al (2018) investigated the implication of politeness strategies used in the classroom interactions. The result showed that the use of politeness strategies in the classroom interactions imply positive results, for instance, it could create effective communication between teacher and students which contain respect value, improve their interactions, and lessen the interference in their communication.…”
Section: Introductionmentioning
confidence: 99%
“…Politeness greatly influences how people do speech acts, such as when a teacher making requests to the students during the class. In the classroom, the teacher surely uses many utterances which display politeness strategies to communicate with students during learning process (Widiadnya et al, 2018). In an EFL (English Foreign Language) classroom, the teacher often asks the students to pay attention to the lessons, to answer a question, or to perform in front of the class to see their ability to use English.…”
Section: Introductionmentioning
confidence: 99%
“…Though, a teacher must also be able to protect their faces, so the teacher's politeness here determines how students respond to requests. Carniasih (2011) as cited in (Widiadnya et al, 2018) states that the students will be motivated by the usage of appropriate politeness strategies. In making requests, the teacher also can apply different politeness strategies so the students are willing to fulfill the teacher's requests.…”
Section: Introductionmentioning
confidence: 99%
“…Last, (I Gusti Ngurah Bagus Yoga et al, 2018) about "The Implications of Politeness Strategies Among Teachers And Students In The Classroom" The participant is a Vocational High school Student. In the discussion, the writer found that politeness makes the learning more comprehensive and certainly a positive environment.…”
Section: Introductionmentioning
confidence: 99%